ELECTRON PROBE MICROANALYSIS OF ENVIRONMENTAL SAMPLES: PREPARATION OF REFERENCE MATERIALS, CORRECTION FOR PARTICLE SIZE EFFECTS AND REPRESENTATIVE RESULTS ON SEDIMENTS RECOVERED FROM SNOW, POWER STATION FLY ASH AND BONE SAMPLES - Pavlova L.A.; Belozerova O.Yu.; Paradina L.Ph. (My University, 2001)
In this paper we report the results of electron probe X-ray microanalysis (EPMA) that was used to study environmental materials. The mode of preparation and certification of reference samples based on a basaltic glass matrix for environmental applications of EPMA is described. These samples were prepared containing scandium, strontium and barium (from 0.03 up to 7% m/m) and an evaluation was made of homogeneity, their stability to local heating, followed by analysis by independent methods for certification of composition. Matrix correction procedures for the EPMA technique have been developed for particles having a size commensurable with the volume of X-ray generation. An analytical equation for the size factor is proposed and two techniques for selecting optimum conditions for the analysis of environmental samples by EPMA are reported. These procedures provided satisfactory results when utilized in analysing sediments recovered from snow, coal fly ash and the bones of animals and fish, results from which can be used as indicators for evaluating the pollution level of the lower atmosphere, surface and ground water, as well as revealing pollution mechanisms.